Personal growth initiative: confirmatory factor analysis, gender invariance, and external validity of the Persian version - Habibi Asgarabad, Mojtaba; Salehi Yegaei, Pardis; Bromandnia, Parishad; Ciarrochi, Joseph; Mastrotheodoros, Stefanos; Wiium, Nora (Frontiers in Psychology, 2025)
IntroductionThe current cross-sectional research was performed to verify the measurement soundness of the Personal Growth Initiative Scale-II (PGIS-II) regarding reliability, validity, and gender invariance in an Iranian sample.MethodsIn an online survey, 1,453 students (50.8% girls, meanage = 15.48, SD = 0.97) were recruited from several high schools located in Tehran to complete the Persian version of PGIS-II, Youth Self-Report (YSR) of internalizing and externalizing behavior problems, and demographic characteristics.ResultsThe original 4-factor structure of PGIS-II demonstrated the best fit in the Confirmatory factor analysis and was invariant across gender. Reliability estimates of this factorial model, including corrected item-total correlation, inter-item correlations, Cronbach’s alpha, Theta, and Omega were good to excellent (e.g., α = 0.86–0.95). Discriminant validity was upheld via the moderate correlation among PGIS-II’s subscales, and through the acceptable levels of average variance extracted. The concurrent validity of the Persian version of PGIS-II and its subscales was supported by their moderate negative correlations with internalizing and externalizing behavioral problems (r = −0.20 to −0.42) and their moderate positive correlations with educational performance (r = 0.21–0.34). Gender differences emerged, such that boys scored higher on PGIS-II and the subscale of using resources.DiscussionOverall, the PGIS-II seems suitable for application in the Persian context to capture personal growth initiative. Clinicians and school counselors should devote attention to the personal growth initiative as a key mechanism to prevent adolescents’ behavior problems and improve academic performance.